ANALISIS EFEKTIVITAS PEMANFAATAN HOTSPOT DI UNIVERSITAS BINA DARMA(Studi Kasus Mahasiswa Manajemen Informatika) - Emigawaty, Emigawaty; Sobri, Muhammad (Universitas Bina Darma, 2012)
Technological developments have made life easier. It can be seen from the sophistication of television sets, mobile phones, computers to household appliances, it makes it easy for anyone inside. Universitas Bina Darma is one of the University has been using information technology to provide convenience to students to access information services. One such technology is the hotspot. The research was conducted at the Universitas Bina Darma with students of Information Management Study Program as its population. In this study there are two types of variables consisting of the independent variables and moderating variables. While the data collected, analyzed by means of correlation and regression analysis SPSS 13.0. Significance Tests Based on the results of Individual Parameters (test statistic t), can be described the results of testing the hypothesis that the use of Hotspot positive effect on the quality of learning. Keywords: Hotspot, Technology, Significance Tests, Individual Parameters